THE PROPHETIC TRADITION AND NUTRITION: ISSUES OF MIXING RAISINS AND DATES - Tamizi, Sumaiyah Mohd (Online Journal of Research in Islamic Studies, 2017)
Raisins and dates are among the fruits mentioned in the Quran and the Prophetic Tradition that are beneficial to man. From the perspective of nutrition, both fruits i.e. raisins and dates contain vitamins and minerals as well as other nutrients in terms of nutritional content. Notwithstanding the Quranic perspective, the Prophetic Tradition highlights interesting issues on consuming raisins and dates mixed together in a drink. The preventive stance of the Prophet regarding the issue of mixing raisins and dates in a drink reflects the legal opinion of Muslim jurists. In this regard, the high level of sugar content in both raisins and dates particularly in the form of mixing drink indicates the harmful affect to human body. Therefore, this article aims to examine the issues of mixing raisins and dates from the perspective of Prophetic Tradition. Nutritional content of both fruits, i.e. raisins and dates, is also examined in correlation to the preventive stance of the Prophet pertaining to the issues of mixing raisins and dates in a drink. The qualitative method of the Prophetic Tradition’s references as well as nutritional content of raisins and dates was applied in this study. Based on reliable facts of the study, it is proposed that the preventive stance to avoid consuming raisins and dates mixed together in a drink is an important step to be taken to maintain the health of human body.